2015
DOI: 10.1111/cdoe.12208
|View full text |Cite
|
Sign up to set email alerts
|

Dental associations with blood mercury in pregnant women

Abstract: ObjectivesThere is curiosity concerning the source of mercury that is absorbed into the mother's blood and which may affect the developing fetus. This study therefore sets out to determine the extent to which dental amalgam (DA) may contribute to total blood mercury (TBHg) levels of pregnant women in the UK.MethodsWhole blood samples and information on diet and socio‐demographic factors were collected from pregnant women (n = 4484) enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC). The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
21
2
Order By: Relevance
“…However, other studies have shown no significant association between blood mercury levels and ADHD incidence among children in Korea (GM=2.4 μg/L), Romania (GM=0.1 μg/L) and the United States (GM=0.4 μg/L) . Although the present study did not have access to individual data on the blood mercury levels of the study population, dental amalgam might be responsible for approximately 6.5% of the variance in blood mercury levels . Berglund estimated that nine or more amalgam restorations can produce an average daily dose of 1.7 μg of inhaled mercury vapour, and only approximately 0.01% of swallowed mercury vapour is absorbed through the gastrointestinal tract .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, other studies have shown no significant association between blood mercury levels and ADHD incidence among children in Korea (GM=2.4 μg/L), Romania (GM=0.1 μg/L) and the United States (GM=0.4 μg/L) . Although the present study did not have access to individual data on the blood mercury levels of the study population, dental amalgam might be responsible for approximately 6.5% of the variance in blood mercury levels . Berglund estimated that nine or more amalgam restorations can produce an average daily dose of 1.7 μg of inhaled mercury vapour, and only approximately 0.01% of swallowed mercury vapour is absorbed through the gastrointestinal tract .…”
Section: Discussioncontrasting
confidence: 61%
“…26,28,29 Although the present study did not have access to individual data on the blood mercury levels of the | 51 study population, dental amalgam might be responsible for approximately 6.5% of the variance in blood mercury levels. 30 Berglund estimated that nine or more amalgam restorations can produce an average daily dose of 1.7 lg of inhaled mercury vapour, and only approximately 0.01% of swallowed mercury vapour is absorbed through the gastrointestinal tract. 31 In our study, it was assumed that the total amount of mercury detected was insufficient to be associated with future ADHD, even in those with six or more amalgam restorations.…”
Section: F I G U R E 2 Schematic Of How the Various Factors Were Inclmentioning
confidence: 99%
“…(b) The analysis of the prenatal blood for mercury took place 19 years after it was collected. Although it is conceivable that this would have biased the results, the levels achieved and the relationships with dietary and other factors such as dental mercury are similar to those found by others (Golding et al, 2013, Golding et al, 2016b). (c) Although we have allowed for a variety of factors associated with mercury levels and/or behaviour, it is possible that there are other confounders that should have been taken into account.…”
Section: Discussionsupporting
confidence: 78%
“…We show elsewhere (Golding et al, 2016b) the way in which the mercury level varied with maternal age (the older the higher the blood Hg), parity (the more previous pregnancies the lower the Hg), maternal education (the more advanced the level the higher the Hg level), prenatal smoking (associated with lower blood mercury), prenatal alcohol (increasing levels of Hg with increasing alcohol intake), and housing tenure (those in owner occupied housing had the highest, and those in public housing had the lowest mean levels of Hg). All these associations were significant at P < 0.0001.…”
Section: Resultsmentioning
confidence: 88%
“…We have shown elsewhere that there were no differences between the women for whom a trace metal result was obtained compared with the rest of the population in relation to their seafood intake or dental treatment ( Golding et al, 2013 , Golding et al, 2016 ). In Table 1 we also show that there was no bias in regard to a variety of social conditions and lifestyles, except that older and/or more educated women were more likely to have had blood taken for trace metal analyses.…”
Section: Resultsmentioning
confidence: 91%